Design Accounting Recording And Financial Reporting System At Asak Salon - Shella Shella; Hendi Hendi (ConCEPt - Conference on Community Engagement Project, 2023)
Smaller size business tends to record their business transaction improperly. The absence of a correct financial statement may affect the decision-making of business owners and the company's future. Asak Salon is a service business without a systemized accounting recording system. This research aims to design an accounting recording and financial reporting system for Asak Salon with Microsoft Access. Primary data collection was by observation and interview. The output of the research is an accounting recording system to input transactions and produce financial statements for the business. The system can assist the business owner in recording transactions and generating financial statements to show business performance in the period. The business owner may use the financial statement as a basis in decision-making for business development in the future.